FUNGSI PENGASUHAN DAN INTERAKSI DALAM KELUARGA TERHADAP KULITAS PERKAWINAN DAN KONDISI ANAK PADA KELUARGA TENAGA KERJA WANITA - Puspitawati, Herien; Setioningsih, Shely Septiana (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
The aim of study was to analyze social supports, parental function, family’s interaction, marital quality, and child’s condition at family of migrant woman worker. The study implemented cross sectional and retrospective study design. The total sample was 47 family of migrant woman workers who had school-age’s children. Data was analyzed by descriptive, Pearson correlation test, independent sample t-test, and regression test. The results found out that families had social support in moderate category and parenting in high category. Husband-wife interaction and father-child interaction falls into the high category, while the mother-child interaction in the moderate category. However, more than half of children had moderate stress and low achievement at school. Mostly families had high marriage quality. Father-child interaction and husband-wife interaction had positive affects to marriage quality. The length of the wife as migrant had negative affects to child’s conditions. However, income had positive affects on the conditions of child.